Non-alcoholic fatty liver disease (NAFLD) and immune response - Adhikari, Khem Bahadur; Tirosh, Oren (Journal of Institute of Medicine Nepal, 2011)
Introduction: Non-alcoholic fatty liver disease (NAFLD) is a chronic liver disease that affects a high proportion of world.s population. This review aims to update latest advances in epidemiology, clinical aspects, pathogenesis, mechanism, immune responses and therapies of NAFLD. Methods: This paper was prepared with reviews of published articles and books. Results: NAFLD, the commonest liver disorder in the world, is closely associated with metabolic syndrome, particularly obesity and insulin resistance. Sedentary lifestyle and poor dietary choices are leading to obesity, subsequently increasing risk for developing metabolic syndrome and NAFLD. NAFLD is characterized with increased lipogenesis, defective mitochondrial and peroxisomal boxidation and/or disability to lipid export from the liver. It can progress to cirrhosis, hepatocellular carcinoma, and liver failure. The development and progression of NAFLD are also affected by diet and genetic factors. Poor immune system cannot overcome proinflammatory cytokines and reactive oxygen species (ROS) which cause oxidative liver injury. Up regulation of perioxisome proliferator activated receptor (PPAR) and disruption of sterol regulatory element binding protein (SREBP) are important targets for pharmacological intervention accompanied with lifestyle modifications. Conclusions: People with obesity, type 2 diabetes mellitus (T2DM), and metabolic syndrome are likely to suffer from NAFLD. Keywords: Cytokine; inflammation; NAFLD; obesity DOI: http://dx.doi.org/10.3126/joim.v32i3.4960 Journal of Institute of Medicine, December, 2010; 32:3 43-53